Triggering and Relationship Between Mine Earthquake Activities and Stress of Earth Tides During Deep Mining - Zhang, Yuezheng; Ji, Hongguang; Wu, Haoyuan (Frontiers in Earth Science, 2022)
In the process of deep mining, the prevention and control of rockbursts, mine earthquakes and other disasters are common problems. The stress of earth tides and its periodic actions should trigger mine earthquakes when the rock masses in critical state of ruptures. In this paper, Yanbei coal mine was taken as research background to explore the triggering effect of solid tide on mine earthquakes occurring in the floor. The relationship between diurnal tidal stress phase and mine earthquake was studied by statistically analyzing the mine earthquake frequency, and the riggering mechanism was also preliminarily discussed. It was found that solid tidal plays a significant role of trigger action in the occurrence of rock burst of floor type. For different levels of mine earthquakes, the tidal stress triggering effect is different, but the overall trend is close. Compared with the components of tidal stress, vertical stress, north-south stress and shear stress, rockburst occurred more at the stage close to 0° and ±180°. For different types of mine earthquakes, the triggered mechanics function of tidal stress is different. Mine earthquakes in the floor mainly include two kinds (gravity control type and horizontal stress control type). The former easily occurs during tidal stress vertical component of the maximum, while the latter easily occurs when the two horizontal component of the maximum. The frequency of the former is larger than that of the latter. The results show that floor seismic is correlated with solid tidal activity of the earth's crust, which provides a new idea for understanding the mechanism and trigger conditions of mine earthquakes.